KOMPARASI KEEFEKTIFAN KERJASAMA SISTER CITY SURABAYA – XIAMEN DENGAN SURABAYA – BUSAN DALAM BIDANG PENDIDIKAN DAN EKONOMI - Nora Putri Heryati; Yessi Olivia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research analyzes the effectiveness of the sister city cooperation between Surabaya - Busan and Surabaya - Xiamen. Along with the progress of globalization, the Surabaya government has been trying to exploit its potential of the city through developing partnerships with several cities in other countries including Xiamen and Busan. This research focuses on the impact of sister city cooperation, especially on the education system development and the economic expansion in Surabaya.This qualitative research used the decoument analysi method and gathered data from journal articles, books, official documents, websites and news portals to analyse the issues. The effectiveness of cooperation between these three countries was explained through the globalist perspective and city diplomacy theory.The results shows that the cooperation in the education sector between Surabaya and Busan was more effective than Surabaya and Xiamen. Implementation of cooperation through routine activities every year has been very influential in improving the quality of human resources and the quality of education of Surabaya. The respective city governments can share knowledge to solve common problems and explore their potentials through the transfer of experience, knowledge and technology.Keywords: Decentralization, Sister City, Globalization, Delegation, City Diplomacy